Factors Affecting the Activity and Stability of Alkaline Phosphatase in a Marine Pseudomonad - Thompson, Linda M. M. (1974)
Conditions optimum for the assay of alkaline phosphatase of marine pseudomonad B-16 (ATCC 19855) and for maintaining the activity of the enzyme have been determined. The pH for optimal activity of the cell-bound enzyme was 9.0, whereas that for the enzyme after its release from the cells exceeded 9.4. Release was effected by first washing the cells in 0.5 M NaCl and then suspending them in 0.5 M sucrose. In the absence of salts, the activity of the cell-bound enzyme decreased rapidly at 25 C and less rapidly at 4 C. This loss of activity could be arrested but not restored by adding Mg(2+). In the presence of Na(+), activity of the cell-bound enzyme dropped to about 50% of that prevailing initially, but in this case adding Mg(2+) restored enzyme activity completely. The activity of the enzyme after its release from the cells into 0.5 M sucrose was approximately 50% of that of the equivalent amount of enzyme in the original cells. This activity was relatively stable at both 25 and 4 C. Adding Mg(2+) to the released enzyme restored its activity to that of the cell-bound form. The synthesis of alkaline phosphatase by the cells was not affected by adding 50 mM inorganic phosphate to the growth medium. The K(m) of the released enzyme for p-nitrophenyl phosphate was found to be 6.1 × 10(−5) M.